(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
For any language learning theory to be comprehensive and instructional in the field of teaching and learning, it should undergo different criteria. In terms of its universality, it should be applied to all the existing natural languages. It should take into consideration the cognitive and non-cognitive factors. It should consider the different contextual factors that should be relevant to all aspects of life. It should take into account the learning process on the basis of its quantitative and qualitative dimensions on the basis of the three learning components (input, competency building, and communicative acts) and the four corresponding evaluative dimensions (quantity, quality, manner, and relation). In fact, the learning process must be dealt with from the very beginning to the end without missing any component. The missing of one or more components in any theory of learning might confuse linguists and practitioners about what makes a theory comprehensive. For instance, we find that the contribution of Behaviourism took into consideration only behaviour. Cognitivism took into account only the cognitive aspect of the process. Constructivism took into consideration only the building up of competency. What is missing is this meaningful communicative involvement among students. On the other hand, learning has been very often reduced into a purely cognitive process, which is not just that. The non-cognitive faculties are also pertinent in such a way as to avoid any failure in the process of learning. The consideration of the students’ contextual variables is another factor that should be highlighted in such a way as to define the learning of a language as being relevant to all aspects of life by relating it to the learner’s context.